2007
DOI: 10.1093/ajcn/85.6.1586
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D and calcium supplementation reduces cancer risk: results of a randomized trial

Abstract: Improving calcium and vitamin D nutritional status substantially reduces all-cancer risk in postmenopausal women. This trial was registered at clinicaltrials.gov as NCT00352170.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
956
6
45

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,286 publications
(1,029 citation statements)
references
References 34 publications
22
956
6
45
Order By: Relevance
“…Supplementation with 1100 IU/day increased serum 25(OH)D to 38 ng/mL. After four years of treatment, the supplemented group had a 60% lower risk of developing cancer than the placebo group [49]. In another randomized trial, the Women's Health Initiative, no effect of calcium and 400 IU vitamin D/day was found on the incidence of colorectal or breast cancer, which were secondary outcomes [50;51].…”
Section: Vitamin D and Oncologymentioning
confidence: 99%
“…Supplementation with 1100 IU/day increased serum 25(OH)D to 38 ng/mL. After four years of treatment, the supplemented group had a 60% lower risk of developing cancer than the placebo group [49]. In another randomized trial, the Women's Health Initiative, no effect of calcium and 400 IU vitamin D/day was found on the incidence of colorectal or breast cancer, which were secondary outcomes [50;51].…”
Section: Vitamin D and Oncologymentioning
confidence: 99%
“…A frequently cited RCT (n = 1179 white women over age 55) 75 demonstrated that supplementation with vitamin D plus calcium resulted in RR of developing cancer of 0.402 (P = 0.01) compared to placebo. The trial, however, had many limitations: industry-funded, secondary analysis of fracture trial, unclear allocation concealment, small number of events reported, efficacy of blinding not described, and outcome was patient reporting of new onset cancers.…”
Section: Rctsmentioning
confidence: 99%
“…Epidemiological studies suggest an increased risk of and mortality from cancer in northern latitudes with reduced UVB exposure, an association possibly mediated by vitamin D (107) . Furthermore, prospective cohorts have demonstrated an inverse association between 25(OH)D and cancers of the colon, breast and prostate (108)(109)(110)(111) with one intervention study reporting a reduced risk of cancer by 60 % (112) with levels >80 nmol/l. Ananthakrishnan et al (12) looked at data from 2809 patients with IBD and a median plasma 25(OH)D level of 65 nmol/l.…”
Section: Vitamin D and Cancer In Crohn's Diseasementioning
confidence: 99%